Faal Paru Statis: [Static Lung Function] - Arief Bakhtiar; Wirya Sastra Amran (Jurnal Respirasi, 2016)
Respiration or breathing is the body’s attempt to meet the needs of O2 in the metabolic process and emit CO2 as a result of intermediary metabolism by lung and respiratory organs together so that the resulting cardiovascular oxygen rich blood. Respiration has three phases: ventilation, diffusion, perfusion. The situation is said to somebody normal lung function if the work process of ventilation, diffusion, perfusion, and the relationship between ventilation to perfusion of the person is in a relaxed state resulted in the partial pressure of arterial blood gas (PaO2 and PaCO2) were normal. Examination of lung function has an important role in assessing a lung function. However, the thing to know that these checks are supporting and quite helpful in making a specific diagnosis. With spirometry examination can be known or determined all the static volume except residual volume and respiratory capacity than the capacity of residual volume that contains components such as total lung capacity and functional residual capacity. Functional residual capacity measured by special methods such as by using the inert gas helium (helium dilution test), N2 washout and bodyplethysmograph. Some static pulmonary function parameters can interpret any kind of disturbance in the lungs. In restrictive disorders in general decreased static lung volumes. While the obstruction interference parameters are quite significant, namely an increase in residual volume (RV), functional residual capacity (FRC) and the ratio of residual volume and total lung capacity (RV/TLC).